2023
DOI: 10.1002/pmic.202200389
|View full text |Cite
|
Sign up to set email alerts
|

Capillary zone electrophoresis‐high field asymmetric ion mobility spectrometry‐tandem mass spectrometry for top‐down characterization of histone proteoforms

Qianyi Wang,
Fei Fang,
Qianjie Wang
et al.

Abstract: Characterization of histone proteoforms with various post‐translational modifications (PTMs) is critical for a better understanding of functions of histone proteoforms in epigenetic control of gene expression. Mass spectrometry (MS)‐based top‐down proteomics (TDP) is a valuable approach for delineating histone proteoforms because it can provide us with a bird's‐eye view of histone proteoforms carrying diverse combinations of PTMs. Here, we present the first example of coupling capillary zone electrophoresis (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“… 19 , 20 , 26 We further boosted the number of identified proteoforms from human cell lines to over 23,000 by coupling LC fractionation to CZE-MS. 3 Most recently, we developed online two-dimensional high-field asymmetric waveform ion mobility spectrometry-CZE-MS (FAIMS-CZE-MS) to benefit the identification of large proteoforms 27 and histone proteoforms. 28 We also showed the capability of CZE-MS for TDP of membrane proteins. 29 The Kelleher group documented the high sensitivity of CZE-MS for TDP and the reasonable complementarity between CZE-MS and LC-MS for proteoform identification.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“… 19 , 20 , 26 We further boosted the number of identified proteoforms from human cell lines to over 23,000 by coupling LC fractionation to CZE-MS. 3 Most recently, we developed online two-dimensional high-field asymmetric waveform ion mobility spectrometry-CZE-MS (FAIMS-CZE-MS) to benefit the identification of large proteoforms 27 and histone proteoforms. 28 We also showed the capability of CZE-MS for TDP of membrane proteins. 29 The Kelleher group documented the high sensitivity of CZE-MS for TDP and the reasonable complementarity between CZE-MS and LC-MS for proteoform identification.…”
Section: Introductionmentioning
confidence: 74%
“…CZE-MS has also been well recognized as an alternative technique to LC-MS for global TDP profiling of proteoforms in cells and tissues due to its high efficiency and sensitivity for proteoform separation and detection as well as its unique opportunity for accurate prediction of proteoform’s μ ef . Several research groups have shown the early examples of CZE-MS for highly sensitive and global TDP of complex biological samples. Our group has shown the identification of hundreds to thousands of proteoforms from complex samples by single-shot CZE-MS measurements via innovations in capillary coating, online proteoform stacking, etc. ,, We further boosted the number of identified proteoforms from human cell lines to over 23,000 by coupling LC fractionation to CZE-MS . Most recently, we developed online two-dimensional high-field asymmetric waveform ion mobility spectrometry-CZE-MS (FAIMS-CZE-MS) to benefit the identification of large proteoforms and histone proteoforms . We also showed the capability of CZE-MS for TDP of membrane proteins .…”
Section: Introductionmentioning
confidence: 99%
“…The Sun group developed SEC-CZE-MS/MS (HCD) and CZE-FAIMS-MS/MS (HCD) for high-capacity separation and highly sensitive TDP measurement of histone proteoforms, leading to the ID of nearly 400 and 600 histone proteoforms from a commercial calf thymus sample. 99,100 PTM localization for TDP analysis continues to pose a hindrance because the production of substantial fragment ions from highly efficient gas-phase fragmentation is vital for confidently mapping the sequence and confirming the PTM information. 101 To accurately localize the PTMs on histone proteoforms, the Brodbelt group integrated UVPD with gas-phase PTCR to achieve up to 91% sequence coverage of calf thymus histone H4 with N-terminal acetylation, K12 acetylation, and R3 dimethylation.…”
Section: Technological Developmentmentioning
confidence: 99%